Inhomogeneous superconductivity and quasilinear magnetoresistance at amorphous LaTiO3/SrTiO3 interfaces. (5th November 2020) - Lebedev, N; Stehno, M; Rana, A; Gauquelin, N; Verbeeck, J; Brinkman, A; Aarts, J
Abstract: We have studied the transport properties of LaTiO3 /SrTiO3 (LTO/STO) heterostructures. In spite of 2D growth observed in reflection high energy electron diffraction, transmission electron microscopy images revealed that the samples tend to amorphize. Still, we observe that the structures are conducting, and some of them exhibit high conductance and/or superconductivity. We established that conductivity arises mainly on the STO side of the interface, and shows all the signs of the two-dimensional electron gas usually observed at interfaces between STO and LTO or LaAlO3, including the presence of two electron bands and tunability with a gate voltage. Analysis of magnetoresistance (MR) and superconductivity indicates the presence of spatial fluctuations of the electronic properties in our samples. That can explain the observed quasilinear out-of-plane MR, as well as various features of the in-plane MR and the observed superconductivity.